ANALISIS VOLUME PERDAGANGAN DAN RETURN SAHAM SEBELUM DAN SELAMA PANDEMI COVID-19 - Lukman, Putri Rismawati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Covid-19 pandemic has impacted the Indonesian capital market significantly. This research aims to identify and analyze the disparities in trading volume and stock returns prior to and during the pandemic within stocks of differing market capitalizations, blue chip and non-blue chip stocks. The sample for this study comprised 20 IDX30 shares and 32 IDX SMC-LIQ shares. The validation of hypotheses was accomplished using the Wilcoxon signed-rank test. The research findings revealed significant differences in trading volume and stock returns before and during the Covid-19 pandemic. The trading volume of both blue chip and non-blue chip stocks experienced an increase, indicating an augmented interest in stock market investment amid the pandemic. The returns on blue chip and non-blue chip stocks exhibited an upswing due to governmental policies engendered a positive sentiment among investors.